Integrating of Quality Function Deployment for Product Design and Development of Portable Shopping Trolley - Melfa Yola (UIN Sultan Syarif Kasim Riau, 2012)
To compete internationally, it is not enough just building a product. Today, customers have a lot of choice to choose one product. Due to this condition, manufacturers need to create a product that satisfy or exceed customers’ needs and expectation. Quality Function Deployment (QFD) is a unique tool that helps a company to plan and design products to meet customers’ needs. QFD is a structured method for product planning that helps a product project team to represent the customers’ needs and then evaluate how and whether the company can meet these needs. The study in this paper presents an implementation of Quality Function Deployment in product design and development phases for developing Portable Shopping Trolley. Three design concepts are built to get the best concept that fulfill customers’ needs and expectation. The result will be presented in drawing and final specification.Keywords : Product Design and Development, Quality Function Deployment, Portable ShoppingTrolley